2020
DOI: 10.3390/nano10010092
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Colorimetric Bacteria Detection Method Utilizing Chitosan-Coated Magnetic Nanoparticles

Abstract: An effective novel strategy to detect bacteria is promising because it may improve human health by allowing early diagnosis and timely treatment of bacterial infections. Here, we report a simple, reliable, and economical colorimetric assay using the peroxidase-like activity of chitosan-coated iron oxide magnetic nanoparticles (CS-MNPs). When CS-MNPs are incubated with a sample containing bacterial cells such as the gram-negative Escherichia coli or the gram-positive Staphylococcus aureus, the negatively-charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…To the best of our knowledge, chitosan stabilized AgNPs have not been previously used for LPS detection. In a recent publication, chitosan-coated iron oxide magnetic nanoparticles were reported for the colorimetric detection of E. coli and the Gram-positive Staphylococcus aureus [49]. A similar electrostatic interaction was observed showing the universality of the nanoparticle-LPS detection.…”
Section: Discussionmentioning
confidence: 64%
“…To the best of our knowledge, chitosan stabilized AgNPs have not been previously used for LPS detection. In a recent publication, chitosan-coated iron oxide magnetic nanoparticles were reported for the colorimetric detection of E. coli and the Gram-positive Staphylococcus aureus [49]. A similar electrostatic interaction was observed showing the universality of the nanoparticle-LPS detection.…”
Section: Discussionmentioning
confidence: 64%
“…As the extinction coefficient of Au nanoparticles is several orders of magnitude larger than those of traditional organic dye molecules, upon formation of Au nanoparticle aggregates, the solution color will change from red to purple for Au nanoparticles, which can be easily visualized by naked eyes. Lei et al reported a simple, reliable, and economical colorimetric assay using the peroxidase-like activity of chitosan-coated iron oxide MNPs [43]. This simple colorimetric strategy allows for the rapid detection of bacterial cells down to 10 4 CFU/mL by the naked eye and 10 2 CFU/mL using spectrophotometry within 10 min.…”
Section: Colorimetric Detectionmentioning
confidence: 99%
“…Magnetic nanoparticles (MNPs) have also been explored for the specific characterization of pathogenic bacteria, as they show remarkable enzyme activity with extremely high stability and they can be mass-produced at low cost. Pathogen-specific receptors like antibodies are therefore conjugated on the surface of the nanoparticles and are utilized to identify bacteria (Le, Tran, & Kim, 2020). Shams et al designed an immunosensor for characterization ofBrucella abortus based on the blue-silica nanoparticles (SiNPs) and paramagnetic nanoparticles (PMNPs).…”
Section: Sandwich Immunoassay Based On the Silica-and Magnetic-nanoparticles For Detection Of Brucellamentioning
confidence: 99%